Can humans be divided into "Hawks" and "Doves"? An evolutionary medicine perspective - Hromatko, Ivana (Array, 2010)
One of the issues within the framework of Darwinian medicine is why individuals develop the specific disease they do? Within a population natural selection maintains the balance in frequency of different genes determining the tendency towards higher (Hawks) or lower aggressiveness (Doves), and it is suggested that these strategies are related to health outcomes. Since the physiological responses to stressful events are different in Hawks and Doves, the aims of this preliminary study were to determine whether an analogue of Hawks and Doves as basic coping strategies can be defined in humans and whether the proportion of Hawks and Doves differs among different groups of patients. 205 patients from various clinical departments participated in the study. Based on their coping style and trait anxiety, two groups of patients were formed: Hawks (low trait anxiety and problem-oriented coping style) vs. Doves (high trait anxiety and avoidant coping style). Although there were no overall differences in proportion of Hawks and Doves between genders, majority of men among gastroenterological and dermatological patients were classified as Hawks, while there were no differences in proportion of Hawks and Doves among women in these groups. Irrespectively of gender, majority of patients in the psychiatric group were categorized as Doves. It seems there is an interaction between gender and allostatic load management, and the onset of a certain disease might be the outcome of this interaction.